Distinct classes of gut bacterial molybdenum-dependent enzymes produce urolithins - Minwoo Bae; Xueyang Dong; Julian Avila-Pacheco; Quyen D. Nguyen; Fechi Inyama; Vayu Hill-Maini; Clary B. Clish; Emily P. Balskus (Proceedings of the National Academy of Sciences, 2025)
Urolithin A is an anti-aging and anti-inflammatory gut bacterial metabolite derived from ellagic acid (EA), a polyphenol abundant in berries and nuts. The conversion of EA to urolithin A involves multiple chemically challenging phenol dehydroxylation steps that produce urolithins with varying bioactivities. Despite their biological and chemical significance, the bacterial enzymes responsible for urolithin production remain largely unidentified. Here, we use differential gene expression analysis, anaerobic protein production, and enzyme assays to identify members of two distinct molybdenum enzyme families (the DMSO reductase family and the xanthine oxidase family) capable of regioselective dehydroxylation and urolithin generation. These two enzyme families have distinct substrate requirements, suggesting they employ different catalytic mechanisms for phenol dehydroxylation. Multiomics analysis of a human cohort uncovers decreased levels of urolithin A and genes encoding urolithin A-producing enzymes in patients with inflammatory bowel disease (IBD), implying reduced health effects of EA consumption in this setting. Together, this study elucidates the molecular basis of urolithin production, expands the known enzymatic repertoire of the human gut microbiome, and suggests a potential link between gut bacterial urolithin production and reduced host inflammation.